MENGKAJI HUBUNGAN ANTARA PENGAWASAN, MOTIVASI BERPRESTASI, KOMPETENSI PROFESIONAL, DAN KINERJA GURU: STUDI KASUS GURU SMP - Irmayanti (PT. Berkah Digital Teknologi, 2023)
Purpose: The aim of this study is to examine the influence of supervision, achievement motivation, and professional competency on teacher performance in Negeri 2 Plered Middle School, Cirebon District. Research Methodology: This study adopts a quantitative approach based on the philosophical framework of logical positivism. A survey method was employed using a 5-point Likert scale questionnaire. The data was collected directly from the teachers of Negeri 2 Plered Middle School. The sample size consisted of 38 teachers selected through a saturated sample technique. Data instrument testing included validity, multicollinearity, and heteroscedasticity tests. Multiple linear regression analysis was conducted to analyze the relationship between the variables. Results: The results indicate that supervision, achievement motivation, and professional competency significantly influence teacher performance. With each unit increase in supervision, achievement motivation, and professional competency, teacher performance increases by 0.593, 0.284, and 0.213, respectively. Limitations: This study is limited to Negeri 2 Plered Middle School in Cirebon District and may not be generalized to other schools or contexts. Additionally, the findings are based on self-reported data, which may be subject to social desirability bias. Contribution: This study contributes to the understanding of the factors that influence teacher performance, specifically in the context of Negeri 2 Plered Middle School. The findings provide insights for educational institutions and policymakers in designing effective supervision strategies, fostering achievement motivation, and enhancing professional competency among teachers to improve overall teacher performance.